Answer:
(0, 7, 9)
Explanation:
The direction vector (a, b, c) is given by B - A
(a, b, c) = (−1, 5, 6) - (-3, 1, 0) = (2, 4, 6)
(a, b, c) = (2, 4, 6)
Let us use point A as
, therefore (-3, 1, 0) =
![(x_o,y_o,z_o)](https://img.qammunity.org/2021/formulas/mathematics/college/hk4773jav9e7gu4k7pxc3f2a1ab2esme0e.png)
![x=x_o+at\\\\x=-3+2t\\\\y=y_o+bt\\\\y=1+4t\\\\z=z_o+ct\\\\z=0+6t](https://img.qammunity.org/2021/formulas/mathematics/college/sfb2482yvixdctt44oyr2fvghgxen23q52.png)
Substituting the value of x, y and z into the plane equation:
2x + y − z + 2 = 0
2(-3+2t) + (1 + 4t) - (6t) + 2 = 0
-6 + 4t + 1 + 4t - 6t + 2 = 0
2t -3 = 0
2t = 3
![\x=-3+2t\\\\x=-3+2(3/2)=0\\\\y=1+4t\\\\y=1+4(3/2)=7\\\\z=0+6t\\\\z=6(3/2)=9\\\\x=0,y=7,z=9\\\\(0,7,9)](https://img.qammunity.org/2021/formulas/mathematics/college/pbyk9lqoc2sjq6ytpn59z106ea627i3avl.png)
t = 3/2